HaTS - Hanover Traffic Scenario for SUMO - Nico Ostendorf; Keno Garlichs; Lars C. Wolf (SUMO Conference Proceedings)
Realistic and comprehensive traffic simulations are essential for the effective testing and evaluation of emerging technologies, such as Vehicle-to-X (V2X) communication, and diverse use cases, particularly within complex urban environments. While current traffic scenarios often focus on motorized vehicles, there is a need to address the safety of vulnerable road users (VRUs), such as pedestrians and cyclists.  This is especially relevant in light of the European Union's Vision Zero initiative, which aims for zero road fatalities by 2050. Although a few pedestrian-focused scenarios exist, there is no scenario specifically addressing bicycle traffic, despite their status as one of the most at-risk VRUs, with stagnant fatality rates in recent years. To address this gap, this paper introduces the Hanover Traffic Scenario for SUMO (HaTS), a novel traffic scenario including motorized vehicles and bicycles. HaTS provides a detailed and accurate representation of the road network, traffic light systems, and buildings within the city center of Hanover, Germany. A key feature of HaTS is its integration of real-world traffic count data for both bicycles and motorized vehicles, enabling a realistic and representative traffic demand representation. Additionally, a novel metric is employed for the parametrization of the scenario, enhancing the alignment between real and simulated traffic volumes. For the validation we compare the results of the HaTS with the real world traffic counts. HaTS is the first open-source SUMO scenario focused on bicycles, providing a realistic representation of the road network and traffic demand, thereby contributing to the advancement of urban traffic simulations.